Study of natural convection heat transfer for a cylindrical and semicylindrical heat transfer system geometry - Zuzana Brodnianská; Stanislav Kotšmíd (Case Studies in Thermal Engineering, 2023)
The paper presents the experimental and numerical study of the heat transfer parameters for the heated tube bank and arc-shaped plate made up of four tubes and four arc protrusions arranged one above the other. To evaluate the local heat transfer coefficients, the holographic interferometry is used as the experimental method, while the numerical simulations are performed by the Ansys Fluent software. The tube bank supplemented by the fin of different thickness and the double arc-shaped plate is further considered to improve the heat transfer parameters and the numerical results are compared with the basic arrangements. Considering the natural convection, the Rayleigh numbers are specified in the range of 16,460 to 46,340. It is observed that the tube bank achieves a higher average Nusselt number in the range of 37%–82% compared with the other arrangements depending on the Rayleigh number. The tube bank with fins does not increase the heat transfer parameters; however, there is an increase in average heat flux compared to the tube bank without fins. The double arc-shaped plate arrangement slightly increases the heat transfer and markedly increases the average heat flux compared to the single one. The highest average heat flux is achieved for the double arc-shaped plate and tube bank with fins in the range of 27.430 Wm-2 to 126.139 Wm-2.